Competitiveness of Jatropha curcas production in the Frailesca region, Chiapas, Mexico - Avila-Soler, Enrique; García-Salazar, José Alberto; Valtierra-Pacheco, Esteban (Instituto de Ecología, A.C., 2018)
In 2007, government of Chiapas began to promote the Jatropha curcas production in La Frailesca, Chiapas for biofuels. The main objective of this study was to determine whether the Jatropha production has comparative advantages and is competitive without government support. The policy analysis matrix methodology was used to analyze the following Jatropha technologies: 1) monocrop in the first four years, 2) monocrop since the fifth year and, 3) polycropping of Jatropha, corn and peanut in the first four years. Results indicate that in the first four years, growers have losses of MXN $5050 ha-1 if Jatropha is produced as monocrop, and they obtain profits from the fifth year of MXN $ 14 719 ha-1. In the first four years the growers obtain profits of MXN $ 13 753 ha-1 if Jatropha is produced in polycropping with corn and peanuts. The cost of domestic resources is 1.14, 0.37 and 0.47 in technologies 1, 2 and 3 respectively, indicating that Jatropha has advantages only from the fifth year. The benefit-cost ratio was 0.92, 1.95 and 1.76 for technologies 1, 2 and 3 respectively, indicating that Jatropha production is competitive in the long run from the fifth year onwards, and in the first four years Jatropha should be associated with corn and peanut to avoid losses. Jatropha production is profitable in Chiapas, therefore it is convenient to promote it.